(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The chilean attorney Juan Egaña showed in his actions and essays a special interest in artistic expressions. Art and the juridical norms must work together and point to a same objective. This article is oriented to show the essentials that confirm that following ideas of Plato, Egaña conceived painting, sculpture, music and architecture put to the service of the organization of the society.